How Authors Manage The Quality of Research and Published Manuscripts Using Digital Applications (Evidence Analysis of International Studies) - Gunawan Widjaja; Novi Puji Lestari; Vani Wirawan; Fachrurazi Fachrurazi; Ita Nurcholifah (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
How writers manage quality study work and manuscripts published using digital applications through searching and analyzing data from several high-impact publications in the field of digital technology literature review has become the primary goal of this study. Because we believe that the success of research work is very closely related to the use of digital technology facilities considering that in the current era, all ease of work is in the application of digital tools, for this, we first conducted a data search using online data based on several well-known journal publications such as the Researchgate database, Elsevier, Google Books, and sage pub. We have looked into everything by including information assessment, information understanding, and information end drawing dependent on the goal to respond to this examination question with legitimacy and certainty. Given the aftereffects of the information and conversation, we can close the outcomes, among others, by fusing innovation into research work; the danger of human errors was diminished while the exploration interaction was sped up. Cloud-based advances started to change the way scholastics gather information numerous many years after the fact. Our development mirrors the developing requirement for fast admittance to great information. Ideally, these discoveries add to the improvement of science and innovation.